G237 Your Future Is In Your Hands (A project for young people living with sickle cell and thalassaemia). (7th April 2014) - Ajayi, A; Marrott, H
Abstract : Purpose: Young people living with sickle cell and thalassaemia are not exempt from the general challenges faced by people of their age, especially those from Black and Minority Ethnic groups. In addition to these are the challenges of their health needs. Some live in isolation within their families and schools and struggle with the stigma associated with their conditions. Certain common psychological issues also hinder them from looking forward to or making plans for their future which might lead to poor achievements. Also there is a trend among some adult patients who transitioned into adulthood feeling unable to progress in life because of their health challenges. Method: 13 young people aged 8 –17 consented. Pre and post questionnaires were used to gather information from the participants and parents on their future in relation to their health challenges. There was 5 sessions in all- bowling as an icebreaker; a team building day; a session to address common fears and anxieties through drama, role play, talks and games; a 4 th on transition, self care, planning for the future, anatomy and physiology, how the body is affected by the conditions and inspirational stories from adult patients. The final session was a celebration of achievements, award of gifts / certificates and feedback of the results to a wider audience of parents and adult service users. Results: The results from the post event questionaires, session evaluation forms and comments from the participants and their parents clearly demonstrated that they enjoyed the sessions; formed new friendships; felt more positive about self and the future; developed more confidence and a 'never giving up' attitude; understood the need to be in control of their condition and keep well; felt better informed about their condition and how to cope with the challenges and the older ones especially felt motivated to plan for their future. Conclusion: The project highlighted that the need for support, not only clinical but social and psychological is required by these young people. Health professionals involved with them have a place in providing guidance, mentoring and motivation early to encourage them to maximise their potentials rather than settle for less.